New species, occurrence records and observations of predation by deep-sea Asteroidea (Echinodermata) from the North Atlantic by NOAA ship Okeanos Explorer - Mah, Christopher L. (Zootaxa, 2020)
Exploratory cruises by the NOAA Ship Okeanos Explorer have resulted in a substantial contribution in our understanding of deep-sea echinoderm biodiversity, biology, and ecology in the North Atlantic. This includes the description and in situ feeding observations of two, new corallivorous goniasterid species, Evoplosoma nizinskiae n. sp. and Sibogaster bathyheuretor n. sp. Significant in situ observations include a synchronous feeding event including multiple goniasterid asteroids and a cidaroid urchin on a large demosponge, providing new data for understanding echinoderm feeding behavior, including agonistic behavior, in deep-sea settings and new, in situ feeding observations for 28 deep-sea species including the myxasterid Pythonaster atlantidis, the korethrasterid Remaster palmatus and the poorly understood hippasterine goniasterids, Gilbertaster caribaea and Sthenaster emmae.